Beyond Erin Brockovich and A Civil Action: Should Strict Products Liability Be the Next Frontier for Water Contamination Lawsuits? - Jim Gash (Washington University Law Quarterly, 2002)
This Article explores the yet unexplored—the viability of strict products liability against sellers of contaminated water. Part I sets the factual context for the Article, briefly describing the nature and scope of this nation’s groundwater contamination problem, and explains why, though historically ignored, strict products liability may figure prominently in current and future water contamination litigation. Part II sets the legal context for the Article, very briefly outlining the evolution of strict products liability from its birth in Greenman v. Yuba Power Products, Inc., through its maturation as urged in the recent Restatement (Third) of Torts: Products Liability (hereafter Restatement Third). Part III then analyzes whether each of the necessary elements of a strict products liability cause of action is sufficiently satisfied to warrant its application to the sale of contaminated water. Part III concludes that contaminated water is properly characterized as a manufacturing defect and thus subjects the seller of the water to strict liability. Part IV traces the historical public policy foundations for imposing strict liability and explores whether its application to the sale of contaminated water furthers or undermines the interests sought to be advanced or protected by strict products liability. Part V then highlights the critical importance of quality control as a pivotal public policy factor in strict products liability. While the absence of quality control as a public policy factor in the design and warning defect context has allowed a return to a negligence-based liability scheme, quality control remains central to the continued application of strict liability in the manufacturing defect context. Part V then illustrates the importance of quality control through a series of graphs depicting the impact of quality control decisions on the number of expected manufacturing defects and their consequential costs. Part V also explains that the almost uniformly-recognized unfairness of imposing strict liability on manufacturers of products containing unforeseeable defects in the design and warning defect contexts also exists in the manufacturing defect context in numerous instances. To remedy that unfairness, Part VI proposes a new affirmative defense to manufacturing defect liability applicable when there is an unforeseeable defect in the product that is not reasonably traceable to the quality control levels set by the manufacturer. Finally, Part VI illustrates the application of the proposed quality control affirmative defense by applying the defense to the facts of A Civil Action and Erin Brockovich.
Keywords: Water pollution; Hazardous substances; Product liability; Strict liability; Government policy; Erin Brockovich; A Civil Action